The Mechanism of Lavender Essential Oil in the Treatment of Acute Colitis Based on “Quantity–Effect” Weight Coefficient Network Pharmacology - Wang, Yao; Zou, Junbo; Jia, Yanzhuo; Zhang, Xiaofei; Wang, Changli; Shi, Yajun; Guo, Dongyan; Wu, Zhenfeng; Wang, Fang (Frontiers in Pharmacology, 2021)
This study aimed to introduce a new weight coefficient combined with network pharmacology to predict the potential active components, action targets, and signal pathways of lavender essential oil, and to investigate the therapeutic effect of lavender essential oil on colitis through animal experiments. The component targets of lavender essential oil were mined from the Pubchem and SwissTargetPrediction databases, and the relative content of lavender essential oil was compared with OB (Oral bioavailability) to establish a "quantity–effect" weight coefficient. Online databases such as GeneCards and String were used to construct a "lavender essential oil compound target disease target" network to extract the key targets of core compounds acting on diseases. The clusterProfiler package in R language programming of Rstudio software was used to analyze the enrichment of the related targets by Gene Ontology (GO) and the KEGG, and the enriched pathways were reordered according to the "quantity–effect" weight coefficient of the targets they participated in. Following up on the findings, the pharmacodynamic test showed that after taking lavender essential oil in mice, the levels of inflammatory cytokines including EGFR, TNF- α, and IFN - γ in serum and colon tissue decreased, and lavender essential oil could mediate Th17 cell differentiation by reducing Dextran sulfate sodium (DSS)-induced Ulcerative Colitis (UC) colonic mucosal damage. The results indicated that lavender essential oil can alleviate DSS-induced colonic mucosal injury in UC mice. Based on the network pharmacology of the " quantity–effect " weight coefficient, this study indicated that lavender essential oil can regulate the level of inflammatory factors, inhibit inflammatory reactions through a multi-component and multi-target strategy, and ultimately alleviate the colonic mucosal injury of UC mice. Through the weight coefficient network pharmacology mining, it was concluded that the Th17 cell differentiation, PI3K-Akt signaling pathway, and Th1 and Th2 cell differentiation of lavender essential oil in the treatment of UC may be the key pathway for the treatment of the disease. Through the establishment of a weight coefficient combined with network pharmacology and the combination of dose and effect, it shows that network pharmacology may provide a better basis for the treatment of disease mechanism.